Toner and method for producing toner
By using crystal ethylene resin and waxy mixture in the color tubing agent, it is difficult to meet the problem of low temperature and high temperature storage stability at the same time, realizing high durability and excellent demand demolition. sex.
Patent Information
- Application Number
- CN202111534169.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-30
- Filing Date
- 2021-12-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-12-15
AI Technical Summary
The existing toners are difficult to satisfy both low-temperature fixing and high-temperature storage stability, and the toner is prone to rupture or fragmentation when wax is added to improve mold release.
By using the crystalline ethylene resin and wax tone particles containing a single unit containing a long -chain alkyl unit, a co -crystal mixture of wax and resin components is formed to improve low temperature and shadowing, high temperature storage, storage of high temperature storage Stability and desertibility, and enhance the durability of the color tone agent.
It achieves excellent low-temperature fixability, high-temperature storage stability, mold release and high durability of the toner, and avoids the problem of cracking or chipping of the toner.
Smart Images

Figure CN114637173B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a toner for an electrophotographic image forming apparatus. Background Art
[0002] In recent years, there has been an increasing demand for energy saving in electrophotographic image forming apparatuses. In order to save energy, a technique for fixing toner at a low temperature has been studied to reduce power consumption in the fixing step.
[0003] The low temperature fixability of the toner can be improved by reducing the glass transition point of the resin component of the toner. However, reducing the glass transition point of the resin component will reduce the high temperature storage stability of the toner. Therefore, this method is unlikely to simultaneously satisfy both the low temperature fixability and the high temperature storage stability of the toner.
[0004] In order to satisfy both the low temperature fixability and high temperature storage stability of the toner, a method of using a crystalline resin in a toner has been studied. The non-crystalline resin commonly used as a resin component of a toner has no obvious endothermic peak in the measurement with a differential scanning calorimeter (DSC). In contrast, a crystalline resin has an endothermic peak in the DSC measurement. Due to the regular arrangement of alkyl groups between or within molecules, crystalline resins rarely soften below their melting points. In crystalline resins with such properties, crystals melt rapidly (sharply melt) at the melting point, and this causes a rapid decrease in viscosity.
[0005] Due to such sharp melting properties, crystalline resins have attracted attention as materials that satisfy both low-temperature fixability and high-temperature storage stability of toners. One known crystalline resin is a crystalline vinyl resin. Crystalline vinyl resins are vinyl polymers having monomer units with long-chain alkyl groups. More specifically, crystalline vinyl resins have a main chain skeleton and long-chain alkyl groups as side chains. Since the long-chain alkyl groups of the side chains are regularly arranged, the crystalline vinyl resins have crystallinity and can be crystallized.
[0006] Japanese Patent Laid-Open No. 2014-130243 discloses a toner including a crystalline vinyl resin having a monomer unit having a long-chain alkyl group.
[0007] The present inventors have studied the toner disclosed in Japanese Patent Laid-Open No. 2014-130243 and found that it is advantageous to further improve the durability of the toner. More specifically, it has been found that the combined use of a crystalline vinyl resin having a monomer unit having a long-chain alkyl group and wax can easily cause cracking or chipping of the toner. Summary of the invention
[0008] One aspect of the present disclosure is to provide a toner that may have excellent low-temperature fixing ability, high-temperature storage stability, and releasability, as well as high durability.
[0009] The present disclosure provides a toner, which includes toner particles containing a resin component and a wax. The resin component contains a vinyl polymer A having a monomer unit A represented by formula (A):
[0010]
[0011] Where R 1 represents H or CH3, and R 2 represents an alkyl group having 18 to 36 carbon atoms,
[0012] In scanning transmission electron microscope observation of a cross section of a toner particle, a backscattered electron image of the cross section of the toner particle is obtained, the brightness of each pixel constituting the backscattered electron image is assigned to one of 256 tones within a brightness range of 0 to 255, and a brightness histogram in which the horizontal axis represents the brightness and the vertical axis represents the pixel value is created,
[0013] The total pixel value C in the brightness range of 0 to 9 and the total pixel value A in the brightness range of 0 to 245 satisfy equation (1):
[0014] 0.000≤C / A≤0.250 (1)
[0015] And when the pixel value in the brightness range of 10 to 245 in the histogram has a maximum value P at brightness X, the range of brightness M-brightness N is 120 to 235, where brightness M represents the brightness at which the pixel value is lower than 20% of the maximum value P for the first time from brightness X to brightness 245, and brightness N represents the brightness at which the pixel value is lower than 20% of the maximum value P for the first time from brightness X to brightness 10.
[0016] One aspect of the present disclosure may provide a toner that may have excellent low-temperature fixing ability, high-temperature storage stability, and releasability, and high durability.
[0017] Further features of the present disclosure will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 ] is an example of a brightness histogram of 256 tones created from a cross-sectional image of toner particles of Toner 1 in an exemplary embodiment of the present disclosure.
[0019] Figure 2 3 is an example of a brightness histogram of 256 tones created from a cross-sectional image of toner particles of the toner 35 in an exemplary embodiment of the present disclosure. DETAILED DESCRIPTION
[0020] Unless otherwise specified, the numerical ranges "above ... and below ..." or "... to ..." used herein refer to numerical ranges including the lower limit and the upper limit. For stepwise numerical ranges, the upper and lower limits of each numerical range can be arbitrarily combined.
[0021] (Meth)acrylate refers to acrylate and / or methacrylate, and (meth)acrylic acid refers to acrylic acid and / or methacrylic acid.
[0022] The monomer unit is a monomer constituting a polymer, and refers to the form of a monomer (polymerizable monomer) after reaction. For example, a carbon-carbon bond region in the main chain formed by polymerization of a vinyl monomer in a polymer is a monomer unit. A vinyl monomer can be represented by formula (Z). A vinyl monomer unit is a constituent unit of a polymer, and is the form of a monomer represented by formula (Z) after reaction.
[0023] A monomer unit may be simply referred to as a "unit".
[0024]
[0025] In formula (Z), R Z1 represents a hydrogen atom or an alkyl group, and R Z2 The term "crystalline resin" refers to a resin having a clear endothermic peak in differential scanning calorimeter (DSC) measurement of a resin, toner particles, or toner (differential scanning calorimeter measurement is also referred to as DSC measurement).
[0026] The crystalline state of a mixture of microcrystals of two or more substances is called the eutectic state.
[0027] <Circumstances leading to the present disclosure and presumed mechanism providing advantages of the present disclosure>
[0028] The present inventors consider that the reason why the durability of the toner according to Patent Document 1 needs to be further improved is as follows.
[0029] A toner containing a polymer having a monomer unit having a long-chain alkyl group as a resin component tends to have excellent low-temperature fixability and high-temperature storage stability. This is probably because the long-chain alkyl groups in the side chains of the polymer are regularly arranged and the crystallinity is easily improved. This may be an advantageous property for reducing the amount of heat required in the fixing step in the electrophotographic image forming method.
[0030] However, it has been found that adding wax to toner to improve release properties can impair the durability of the toner. More specifically, it has been found that the toner can easily crack or break. The reason for the cracking or breaking of the toner is that the resin component and the wax in the toner particles can easily crystallize separately and can easily form a wax domain having a clear boundary with the resin component.
[0031] In the brightness histogram of the cross section of the toner particle, a low brightness peak corresponding to the wax and a high brightness peak corresponding to the crystalline vinyl resin having a monomer unit having a long-chain alkyl group are independently observed. Figure 2 An example of a brightness histogram is shown. This shows that the resin component and the wax in the toner particles have clear boundaries and are independent.
[0032] Therefore, the present inventors have proposed the idea of forming a eutectic mixture of wax and resin component so that in the brightness histogram of the cross section of the toner particle, it is difficult to separate the peak corresponding to the resin component from the peak corresponding to the wax, and thus the peak of the resin component is broadened. The present inventors believe that this makes it difficult to have a clear boundary between the resin component and the wax without impairing the releasability exhibited by the wax, and makes it easy to produce a toner with high durability.
[0033] As a result of studies based on these considerations, the present inventors have found that a toner having the above-described constitutional features tends to have excellent low-temperature fixability, high-temperature storage stability, and releasability, and high durability. The constitutional features are described in detail below.
[0034] <Brightness Histogram of Cross Section of Toner Particle>
[0035] The toner is characterized in that, in a brightness histogram according to the present disclosure created by observation through a scanning transmission electron microscope, when a pixel value in a brightness range of 10 to 245 in the histogram has a maximum value P at brightness X, a range of brightness M-brightness N is 120 to 235, wherein brightness M represents the brightness at which the pixel value is lower than 20% of the maximum value P for the first time from brightness X to brightness 245, and brightness N represents the brightness at which the pixel value is lower than 20% of the maximum value P for the first time from brightness X to brightness 10.
[0036] Under the conditions for obtaining a cross-sectional image of a toner particle described later, in a dark field image of the cross section of the toner particle, the portion including the wax is dark, and the portion including the resin component is relatively bright. The brightness of each pixel constituting the cross-sectional image of the toner particle is assigned to one of 256 tones in a brightness range of 0 to 255 to create a brightness histogram in which the horizontal axis represents the brightness and the vertical axis represents the pixel value. In the brightness histogram, the pixel value has a maximum value P at the brightness X in the brightness range of 10 to 245 between the darkest brightness 0 and the brightest brightness 255. The brightness X at the maximum value P in the above range is the brightness at the maximum pixel value among the brightness values corresponding to the portion mainly composed of the resin component of the toner. As described later, the brightness histogram in the present disclosure is created from an image obtained when the brightness X is 150. More specifically, when the measure at the maximum pixel value is 150 among the brightness values corresponding to the portion mainly composed of the resin component, a brightness histogram can be created. The brightness corresponding to the portion mainly composed of the resin component in the brightness histogram can be determined by matching the brightness histogram with the toner particle cross-sectional image. This is because the portion occupying the largest area in the toner particle cross-sectional image generally corresponds to the resin component.
[0037] Pixels with brightness of 246 or more may have noise such as white areas, and are excluded.
[0038] In the brightness histogram, lower brightness indicates darker, and higher brightness indicates brighter. Therefore, pixels in the brightness range of 0 to 9 correspond to individual waxes. Pixels in the brightness range of 10 to 245 correspond to resin components and eutectic structures of wax and resin components. As used herein, the term "individual wax" refers to a wax having a clear boundary with a resin component.
[0039] In addition, the range of brightness M-brightness N is 120 to 235, where brightness M represents the brightness at which the pixel value first falls below 20% of the maximum value P from brightness X to brightness 245, and brightness N represents the brightness at which the pixel value first falls below 20% of the maximum value P from brightness X to brightness 10.
[0040] The value of brightness M-brightness N indicates how wide the peak having the maximum pixel value P at brightness X is. A larger value of brightness M-brightness N indicates a larger number of eutectic structures of the wax and the resin component in the toner particles. The eutectic structure in the toner particles can prevent the resin component and the wax from having a clear boundary without impairing the releasability of the toner, and the toner can easily have high durability.
[0041] More specifically, when the value of lightness M-lightness N is 120 or more, the toner can easily have high releasability and durability. Therefore, the value of lightness M-lightness N is 120 or more, preferably 150 or more. The upper limit is, but not limited to, 235 or less, more preferably 200 or less, and even more preferably 180 or less.
[0042] When the value of brightness M-brightness N is 119 or less, demolding property or durability may be insufficient. The small value of brightness M-brightness N may be caused by the following (1) and / or (2). (1) In the toner particles, the wax and the resin component are completely mixed together. (2) In the toner particles, the wax has a clear boundary in the resin component.
[0043] In the case of (1), a peak corresponding to the mixture of wax and resin component is observed in the brightness histogram. The mixture of wax and resin component has fewer starting points of cracking or breaking of the toner, which is advantageous for durability. However, the wax mixed with the resin component is less likely to ooze out to the toner surface while fixing, and tends to cause a decrease in release properties.
[0044] In the case of (2), as described above, the toner is likely to have cracks or breaks, and low durability.
[0045] The value of brightness M-brightness N can be controlled within the above range via the type and addition amount of the wax or by heat treatment to form a eutectic mixture of the wax and the resin component.
[0046] In the heat treatment, the wax and the resin component may be heated to a molten state, and then may be maintained at a temperature that preferentially crystallizes the wax. More specifically, the wax and the resin component may be maintained at a temperature that is lower than the melting point of the wax and higher than the melting point of the resin component. In such a case, in a mixture of the wax and the resin component, crystallization proceeds under conditions suitable for the wax, and the toner particles may easily have a eutectic structure.
[0047] Even without heat treatment, use of a large amount of an ester wax having a plurality of long-chain alkyl groups and having a branched structure such as dipentaerythritol hexabehenate results in a value of brightness M - brightness N within a preferred range.
[0048] In the brightness histogram, the total pixel value C in the brightness range of 0 to 9 and the total pixel value A in the brightness range of 0 to 245 satisfy equation (1):
[0049] 0.000≤C / A≤0.250 (1)
[0050] As described above, in the brightness histogram, the total pixel value in the brightness range of 0 to 9 corresponds to the individual wax. The equation (1) is satisfied, that is, the smaller the amount of the individual wax in the toner particles is, the fewer the starting points of the cracking or breaking of the toner are, and a toner with high durability tends to be obtained. The equations (2), (3), or (4) may be satisfied.
[0051] 0.000≤C / A≤0.100 (2)
[0052] 0.000≤C / A≤0.080 (3)
[0053] 0.000≤C / A≤0.040 (4)
[0054] <Resin component>
[0055] The resin component may be a binder resin. More specifically, the toner may have toner particles including a binder resin and a wax, and the binder resin may include a vinyl polymer A having a monomer unit A represented by formula (A).
[0056] <Vinyl polymer A and monomer unit A>
[0057] The vinyl polymer A has a monomer unit A represented by the formula (A):
[0058]
[0059] Where R 1 represents H or CH3, and R 2 It represents an alkyl group having 18 to 36 carbon atoms.
[0060] The long-chain alkyl group (alkyl group having 18 to 36 carbon atoms) of the monomer unit A of the vinyl polymer A in the side chain of the vinyl polymer A tends to improve the crystallinity of the vinyl polymer A and tends to provide a toner having excellent low-temperature fixability and high-temperature storage stability. In addition, the vinyl polymer A may be a crystalline resin having a clear endothermic peak in DSC measurement.
[0061] The monomer unit A can be introduced as a monomer unit of the vinyl polymer A by vinyl polymerization of a polymerizable (meth)acrylate monomer having an alkyl group having 18 to 36 carbon atoms.
[0062] Examples of the (meth)acrylate having an alkyl group having 18 to 36 carbon atoms include (meth)acrylate having a linear alkyl group having 18 to 36 carbon atoms [e.g., stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, cetyl (meth)acrylate, dioctadecyl (meth)acrylate, myricyl (meth)acrylate, and tridecyl (meth)acrylate] and (meth)acrylate having a branched alkyl group having 18 to 36 carbon atoms [e.g., 2-decyltetradecyl (meth)acrylate].
[0063] Among them, from the viewpoint of low temperature fixability and high temperature storage stability of the toner, the (meth)acrylate having an alkyl group having 18 to 36 carbon atoms may be a (meth)acrylate having a linear alkyl group having 18 to 36 carbon atoms, a (meth)acrylate having a linear alkyl group having 18 to 30 carbon atoms, or a linear stearyl (meth)acrylate or a linear behenyl (meth)acrylate. Therefore, in formula (A), R 2 Preferably, it represents a straight-chain alkyl group having 18 to 36 carbon atoms, more preferably a straight-chain alkyl group having 18 to 30 carbon atoms, and still more preferably an alkyl group having 18 to 22 carbon atoms. 1 It may be hydrogen.
[0064] The polymerizable monomer forming the monomer unit A (hereinafter also referred to as monomer (a)) or the monomer unit A may be used alone or in combination of two or more thereof.
[0065] The content range of monomer unit A in vinyl polymer A is preferably 20.0 mass % to 80.0 mass %. When the content of monomer unit A is 20.0 mass % or more, the toner tends to have excellent low temperature fixability and high temperature storage stability. Therefore, the content of monomer unit A is preferably 20.0 mass % or more, more preferably 40.0 mass % or more, and more preferably 45.0 mass % or more. When the content of monomer unit A is 80.0 mass % or less, the toner tends to have appropriate elasticity. Therefore, the content of monomer unit A is preferably 80.0 mass % or less, more preferably 75.0 mass % or less, and more preferably 60.0 mass % or less.
[0066] The content of the monomer unit A is the total amount of all monomer units represented by the formula (A). The same applies to the plurality of monomers (a).
[0067] The content of the vinyl polymer A in the resin component is preferably 30.0% by mass or more. When the content of the vinyl polymer A is 30.0% by mass or more, the toner tends to have excellent low-temperature fixability and high-temperature storage stability. Therefore, the content of the vinyl polymer A is preferably 30.0% by mass or more, more preferably 40.0% by mass or more, still more preferably 60.0% by mass or more, and further more preferably 80.0% by mass or more. Still more preferably, the content of the vinyl polymer A is 100.0% by mass, that is, the resin component is only the vinyl polymer A. The upper limit is, but not limited to, 100.0% by mass.
[0068] The weight average molecular weight (Mw) of the vinyl polymer A is preferably in the range of 10,000 to 200,000, more preferably 20,000 to 150,000, still more preferably 40,000 to 70,000. Mw in the above range tends to obtain a toner having appropriately controlled elasticity.
[0069] Further, from the viewpoint of low-temperature fixability, the melting point of the vinyl polymer A is preferably within a range of 50°C to 80°C.
[0070] <Other monomer units>
[0071] The vinyl polymer A may have a monomer unit other than the monomer unit A in order to appropriately control the physical properties of the toner.
[0072] Regarding the vinyl polymer A having other monomer units, the corresponding polymerizable monomer (hereinafter also referred to as other monomer) can be introduced as a monomer unit of the vinyl polymer A by vinyl polymerization.
[0073] Examples of other monomers include the following monomers, which may be used alone or in combination.
[0074] • Monomers having a nitrile group, such as acrylonitrile and methacrylonitrile.
[0075] Monomers having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate.
[0076] • A monomer having an amide group, such as acrylamide and a monomer produced by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having an ethylenically unsaturated bond and having 2 to 30 carbon atoms (acrylic acid, methacrylic acid, etc.).
[0077] Monomers having a carbamate group: For example, a monomer having an ethylenically unsaturated bond and having 2 to 22 carbon atoms (2-hydroxyethyl methacrylate, vinyl alcohol, etc.) and an isocyanate having 1 to 30 carbon atoms [monoisocyanate compounds (benzenesulfonyl isocyanate, toluenesulfonyl isocyanate, phenyl isocyanate, p-chlorophenyl isocyanate, butyl isocyanate, hexyl isocyanate, tert-butyl isocyanate, cyclohexyl isocyanate, octyl isocyanate, 2-ethylhexyl isocyanate, dodecyl isocyanate, adamantyl isocyanate, 2,6-dimethylphenyl isocyanate, 3,5-dimethylphenyl isocyanate, 2,6-dipropylphenyl isocyanate, etc.) , aliphatic diisocyanate compounds (trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, etc.), alicyclic diisocyanate compounds (1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated tetramethylxylylene diisocyanate cyanate, etc.), or aromatic diisocyanate compounds (phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, xylylene diisocyanate, etc.); and an alcohol having 1 to 26 carbon atoms (methanol, ethanol, propanol, isopropanol, butanol, tert-butyl alcohol, amyl alcohol, heptanol, octanol, 2-ethylhexanol, nonanol, decanol, decanol, etc.) A monomer formed by reacting a nonadecanol, a monodecyl alcohol, a lauryl alcohol, a dodecanol, a myristyl alcohol, a pentadecanol, a cetyl alcohol, a heptadecanol, a stearyl alcohol, an isostearyl alcohol, an acetylene alcohol, an oleyl alcohol, a linoleyl alcohol, a linoleyl alcohol, a nonadecanol, a heneicosyl alcohol, a behenyl alcohol, a sinapyl alcohol, etc.) with an isocyanate having an ethylenically unsaturated bond and having 2 to 30 carbon atoms [2-isocyanatoethyl (meth)acrylate, 2-(0-[1'-methylpropynylamino]carboxylamino)ethyl (meth)acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate, etc.].
[0078] Monomers having a urea group: For example, monomers produced by reacting an amine having 3 to 22 carbon atoms [primary amines (such as n-butylamine, tert-butylamine, propylamine, and isopropylamine), secondary amines (such as di-n-ethylamine, di-n-propylamine, and di-n-butylamine), aniline, cyclohexylamine, etc.] with an isocyanate having an ethylenically unsaturated bond and having 2 to 30 carbon atoms.
[0079] Vinyl esters: for example, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprylate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, and vinyl octanoate.
[0080] Monomers having a carboxyl group: for example, methacrylic acid, acrylic acid, and 2-carboxyethyl (meth)acrylate.
[0081] (Meth)acrylates, for example methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.
[0082] Styrene
[0083] ·α-Methylstyrene
[0084] In particular, monomers having a nitrile group can be used. These monomers can be used to easily control the melting point without excessively reducing the crystallinity of the vinyl polymer A, and to produce a toner having excellent low-temperature fixability and high-temperature storage stability. In addition, ethyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, or styrene can be used to appropriately control the elasticity of the toner.
[0085] <Resins other than vinyl polymer A>
[0086] The resin component other than the vinyl polymer A of the toner may be a vinyl resin other than the vinyl polymer A, a polyester, a polyurethane, or an epoxy resin. In particular, from the viewpoint of electrophotographic characteristics, a vinyl resin other than the vinyl polymer A, a polyester, or a polyurethane may be used.
[0087] The monomers constituting the vinyl resin other than the vinyl polymer A may be the monomers other than the above-mentioned monomer (a). Two or more of these monomers may be used in combination as necessary.
[0088] Polyesters can be produced by polycondensation of dibasic or polybasic carboxylic acids (polycarboxylic acids) and polyols.
[0089] Examples of polycarboxylic acids include
[0090] For example, dibasic acids such as succinic acid, adipic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, malonic acid, and dodecenylsuccinic acid, and their anhydrides and lower alkyl esters; aliphatic unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid; and 1,2,4-benzenetricarboxylic acid and 1,2,5-benzenetricarboxylic acid, and their anhydrides and lower alkyl esters. These can be used alone or in combination.
[0091] Examples of polyols include
[0092] Alkylene glycols (ethylene glycol, 1,2-propylene glycol, and 1,3-propylene glycol); alkylene ether glycols (poly(ethylene glycol) and poly(propylene glycol)); alicyclic diols (1,4-cyclohexanedimethanol); bisphenols (bisphenol A); and alkylene oxide (ethylene oxide and propylene oxide) adducts of alicyclic diols. The alkyl moieties of the alkylene glycols and alkylene ether glycols may be linear or branched. In the present disclosure, an alkylene glycol having a branched structure may also be used. Further examples include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol. These may be used alone or in combination.
[0093] In order to adjust the acid value and the hydroxyl value, a monobasic acid such as acetic acid or benzoic acid, or a monohydric alcohol such as cyclohexanol or benzyl alcohol may be used as necessary.
[0094] The polyester can be produced by any method such as an ester exchange method or a direct polycondensation method.
[0095] Polyurethane can be produced by the reaction between a diol component and a diisocyanate component.
[0096] Examples of the diisocyanate component include aromatic diisocyanates having 6 to 20 carbon atoms (excluding carbon atoms of NCO groups; the same below), aliphatic diisocyanates having 2 to 18 carbon atoms, and alicyclic diisocyanates having 4 to 15 carbon atoms, and modified products of these diisocyanates (products modified with a carbamate group, a carbodiimide group, an allophanate group, a urea group, a biuret group, a uretdione group, a uretonimine group, an isocyanurate group, or an oxazolidinone group; hereinafter also referred to as "modified diisocyanates"), and mixtures of two or more thereof.
[0097] Examples of aromatic diisocyanates include meta- and / or para-xylylene diisocyanate (XDI) and α,α,α′,α′-tetramethylxylylene diisocyanate.
[0098] Examples of the aliphatic diisocyanate include ethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), and dodecamethylene diisocyanate.
[0099] Examples of the alicyclic diisocyanate include isophorone diisocyanate (IPDI), dicyclohexylmethane-4,4′-diisocyanate, cyclohexylene diisocyanate, and methylcyclohexylene diisocyanate.
[0100] In particular, it is possible to use an aromatic diisocyanate having a carbon number of 6 to 15, an aliphatic diisocyanate having a carbon number of 4 to 12, and an alicyclic diisocyanate having a carbon number of 4 to 15. In particular, it is possible to use XDI, IPDI, and HDI.
[0101] In addition to the diisocyanate component, a trivalent or higher-valent isocyanate compound may be used.
[0102] The diol component that can be used for the polyurethane may be a diol that can be used for the polyester.
[0103] <Wax>
[0104] The wax in the toner particles may be an ester wax. One or two or more ester waxes may be used.
[0105] The ester wax in the present disclosure only needs to have at least one ester bond in its molecule, and may be a natural ester wax or a synthetic ester wax.
[0106] Examples of ester waxes include, but are not limited to:
[0107] Esters of monohydric alcohols and monocarboxylic acids, such as behenyl behenate, stearyl stearate, and palmityl palmitate;
[0108] Esters of dicarboxylic acids and monohydric alcohols, for example dibehenyl sebacate;
[0109] Esters of glycols and monocarboxylic acids, for example ethylene glycol distearate and hexylene glycol dibehenate;
[0110] Esters of trihydric alcohols and monocarboxylic acids, for example glyceryl tribehenate;
[0111] Esters of tetrahydric alcohols and monocarboxylic acids, such as pentaerythritol tetrastearate and pentaerythritol tetrapalmitate;
[0112] Esters of hexahydric alcohols and monohydric carboxylic acids, such as dipentaerythritol hexastearate, dipentaerythritol hexapalmitate, and dipentaerythritol hexabehenate;
[0113] Esters of polyfunctional alcohols and monocarboxylic acids, such as polyglycerol behenate; and
[0114] Natural ester waxes such as carnauba wax and rice wax.
[0115] The ester wax can be an ester of an alcohol and an aliphatic monocarboxylic acid. 2The carbon atom number Ac of the linear alkyl group represented by and the average carbon atom number Wc of the linear alkyl groups contained in the ester wax may satisfy the formula (5).
[0116] |Ac-Wc|≤6.0 (5)
[0117] In the present disclosure, a straight chain alkyl group does not include an alkylene group or a branched alkyl group.
[0118] Satisfying the formula (5) promotes the formation of a eutectic mixture of the ester wax and the vinyl polymer A, and promotes the production of a toner having high releasability and durability. The present inventors believe that the formation of a eutectic mixture of the ester wax and the vinyl polymer A is promoted because the vinyl polymer A has a linear alkyl chain of similar length and the wax can easily form a stable crystal structure not only in a state where the ester wax and the vinyl polymer A are completely separated and crystallized individually, but also in a state where the ester wax and the vinyl polymer A are entangled with each other. |Ac-Wc| is more preferably 4.0 or less, and even more preferably 2.0 or less.
[0119] When monomer unit A has multiple R 2 When R in monomer unit A is a linear alkyl group, Ac is calculated as follows. 2 Contains X a The mass% of carbon atoms is n a A linear alkyl group, and Y a The mass% of carbon atoms is m a When the linear alkyl group is , use formula (6) to calculate Ac:
[0120] Ac=(n a X a +m a Y a ) / 100 (6)
[0121] For a plurality of ester waxes, |Ac-Wc| is calculated using the Wc of each ester wax relative to the calculated Ac, and it is checked whether |Ac-Wc| of each ester wax is within the above range. Ester waxes having |Ac-Wc| within the above range may be included. Ester waxes having |Ac-Wc| outside the above range may be included.
[0122] In the present disclosure, the ester wax may be an ester of a trivalent or higher polyol and an aliphatic monocarboxylic acid, or an ester of a tetravalent or higher polyol and an aliphatic monocarboxylic acid, or an ester of a hexavalent or higher polyol and an aliphatic monocarboxylic acid.
[0123] The valence of the trivalent or higher polyol corresponds to the number of branched structures of the ester wax. The use of a wax having a branched structure promotes the formation of a eutectic mixture of the vinyl polymer A and the wax, and tends to improve durability and mold release. The reason for promoting the formation of the eutectic mixture may be that the R of the monomer unit A in the vinyl polymer A 2 Due to the branching of wax, it can easily enter the gaps between wax crystals. In addition, due to the R 2 , so that the wax in the toner particles can easily have a network structure. Therefore, the wax and the resin component are less likely to have a clear boundary, and there are fewer starting points for the cracking or breaking of the toner.
[0124] The toner particles may further contain a hydrocarbon wax. One or two or more hydrocarbon waxes may be used.
[0125] Examples of hydrocarbon waxes include, but are not limited to:
[0126] Aliphatic hydrocarbon-based waxes: low molecular weight polyethylene, low molecular weight polypropylene, low molecular weight olefin copolymers, and Fischer-Tropsch waxes, and waxes produced by oxidation and acid addition of these waxes.
[0127] The mass ratio of wax to resin component preferably ranges from 1.0% to 25.0% by mass. When the mass ratio is 1.0% by mass or more, the toner tends to have excellent demoulding properties. Therefore, the mass ratio is preferably 1.0% by mass or more, more preferably 2.0% by mass or more, and even more preferably 5.0% by mass or more. A mass ratio of 25.0% by mass or less is unlikely to result in an excessive amount of independent wax in the toner particles and the rupture or fragmentation of the toner. Therefore, the mass ratio is preferably 25.0% by mass or less, more preferably 20.0% by mass or less, and even more preferably 15.0% by mass or less. When the toner particles contain a plurality of waxes, the mass ratio is calculated using the total mass of the wax.
[0128] The molecular weight of the wax is preferably in the range of 1000 to 3000. Wax having a molecular weight of 1000 or more is difficult to be compatible with the vinyl polymer A, and the toner tends to have excellent low temperature fixability, high temperature storage stability, and mold release. Therefore, the molecular weight is preferably 1000 or more, more preferably 1500 or more. When the molecular weight is 3000 or less, the toner can easily maintain appropriate mold release. Therefore, the molecular weight is preferably 3000 or less, more preferably 2500 or less.
[0129] The melting point of the wax may be higher than that of the vinyl polymer A contained in the toner. When the melting point is controlled as described above, and heat treatment is performed in a toner production process as described later, the toner can easily satisfy the above range of brightness M-brightness N.
[0130] The melting point of the wax is preferably in the range of 60° C. to 120° C. The wax having a melting point in this range can melt and easily seep out to the surface of the toner particles at the same time of fixing. The melting point is more preferably in the range of 70° C. to 100° C.
[0131] <Core-shell structure>
[0132] The toner according to the present disclosure may have a core including a resin component and a wax, and a shell phase covering the core.
[0133] The shell phase may be formed of a resin that can be used as the resin component as described above, other than the vinyl polymer A. In particular, a vinyl resin or a polyester may be used in terms of charging stability.
[0134] <Various additives>
[0135] The toner may contain one or more additives selected from a colorant, a magnetic material, a charge control agent, and a fluidizing agent as necessary. Various additives used in the toner are described in detail below.
[0136] <Colorant>
[0137] Examples of colorants include:
[0138] Yellow colorants such as condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds; more specifically, CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 109, 110, 111, 128, 129, 147, 155, 168, and 180;
[0139] Magenta colorants such as condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinones, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds; more specifically, CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, and 254; and
[0140] Cyan colorants such as copper phthalocyanine compounds and derivatives thereof, anthraquinone compounds, and basic dye lake compounds; more specifically, CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66.
[0141] The colorant used in the toner according to the present disclosure is selected based on hue angle, color saturation, brightness value, light fastness, OHP transparency, and dispersibility in toner particles.
[0142] When the colorant is not composed of magnetic particles, 100.0 parts by mass of the resin component preferably contains 1.0 to 20.0 parts by mass of the colorant. When the colorant is composed of magnetic particles, 40.0 to 150.0 parts by mass of the colorant is preferably added to 100.0 parts by mass of the resin component.
[0143] <Charge Control Agent>
[0144] Any charge control agent may be used.
[0145] Examples of negative charge control agents include
[0146] Monoazo metal compounds, acetylacetonate metal compounds, aromatic hydroxycarboxylic acids, aromatic dicarboxylic acids, hydroxycarboxylic acids, and dicarboxylic acid metal compounds.
[0147] Examples of the positive charge control agent include quaternary ammonium salts, polymer compounds having a quaternary ammonium salt in a side chain, guanidine compounds, pyridine compounds, nigrosine-based compounds, and imidazole-based compounds.
[0148] 100.0 parts by mass of the toner particles preferably contains 0.01 to 20.0 parts by mass, more preferably 0.5 to 10.0 parts by mass of the charge control agent.
[0149] <External Additives>
[0150] Examples of external additives include
[0151] Inorganic fine particles selected from the group consisting of silica fine particles, alumina fine particles, and titania fine particles, and composite oxides thereof. Examples of composite oxides include silica-aluminum fine particles and strontium titanate fine particles.
[0152] 100 parts by mass of the toner particles preferably contain 0.01 to 8.0 parts by mass, more preferably 0.1 to 4.0 parts by mass of the external additive.
[0153] <Toner Production Method>
[0154] The toner and toner particles may be produced by any method including a pulverization method, a suspension polymerization method, an emulsion aggregation method, or a dissolution suspension method. In particular, a suspension polymerization method may be used.
[0155] In order to satisfy the above range of brightness M-brightness N, the content of the vinyl polymer A and the content of the wax may be controlled, and the toner particles may be heat treated at a temperature between the melting points of the vinyl polymer A and the wax for more than 30 minutes.
[0156] Therefore, the method for producing a toner according to the present disclosure includes the following steps:
[0157] producing toner base particles comprising a wax and a resin component, and
[0158] The toner particles are produced by heat-treating the toner base particles in a temperature range of TmA to TmW for 30 minutes or more, wherein TmW represents the melting point of the wax and TmA represents the melting point of the vinyl polymer A.
[0159] In order to easily satisfy the range of brightness M-brightness N, the content of the vinyl polymer A in the resin component is preferably 30.0 mass % or more, and the content of the wax is preferably in the range of 1.0 mass % to 25.0 mass % of the mass of the resin component.
[0160] Furthermore, at a heat treatment temperature within the range of TmA to TmW, the wax crystallizes preferentially over the vinyl polymer A, the toner particles easily have a eutectic structure of the wax and the vinyl polymer A, and the value of brightness M-brightness N tends to increase. TmA may be lower than TmW.
[0161] In addition, the temperature of the toner particles before the heat treatment step may be TmW or higher. In such a case, the vinyl polymer A and the wax in the toner particles can be easily melted, and in the subsequent heat treatment step, crystallization proceeds under conditions suitable for the wax in the mixture of the wax and the resin component, and a eutectic structure can be easily formed.
[0162] In addition, heat treatment for 30 minutes or more enables the wax in the toner particles to be preferentially and fully crystallized. Therefore, 30 minutes or more is preferred, 1 hour or more is more preferred, and 2.5 hours or more is still more preferred. The upper limit is preferably, but not limited to, 5 hours or less.
[0163] <Toner Particle Production Step>
[0164] The step of producing toner particles may be a step of producing toner particles by suspension polymerization. In the production of toner particles by suspension polymerization, a polymerizable monomer composition comprising a polymerizable monomer, a wax, and an optional colorant, etc., is added to an aqueous medium, and the polymerizable monomer composition is granulated in the aqueous medium to form particles of the polymerizable monomer composition. The polymerizable monomer in the particles of the polymerizable monomer composition may be polymerized to produce a resin component, and thus toner particles are produced.
[0165] The production step of toner particles can be a step of producing toner particles by a pulverization method. In the production of toner particles by a pulverization method, first, a toner component such as a resin material containing a vinyl polymer A, a wax, and an optional colorant is mixed. The mixture is fully mixed in a mixer such as a Henschel mixer or a ball mill. Then, the mixture is melted with a hot mixer such as a roller, a mixer, or an extruder. The material is dispersed in the mixed mixture. After cooling and solidification, pulverization and classification are performed to produce toner particles.
[0166] The step of producing toner particles may be a step of producing toner particles by an emulsion aggregation method. In the production of toner particles by the emulsion aggregation method, an aqueous dispersion of each resin material including a vinyl polymer A, a wax, and an optional colorant, etc. is prepared (aqueous dispersion step). Then, the aqueous dispersion is mixed and aggregated to a desired particle size using a metal salt, etc. (aggregation step). The aggregate is heated and fused (heating and fusing step) and then subjected to a cooling step, as well as a washing and drying step, to produce toner particles.
[0167] The production step of the toner particles can be a step of producing toner particles by a dissolution suspension method. In the production of toner particles by the dissolution suspension method, first, a resin material, wax, and optional coloring agent, etc. containing a vinyl polymer A are dissolved or dispersed in an organic solvent (resin dissolution step). Then, the solution or dispersion is dispersed in a poor solvent such as water, approximately to the size of the toner particles, to produce a granulated product (liquid droplets) (granulation step). The toner particles can be produced by distilling out the organic solvent contained in the granulated product (solvent removal step), followed by washing and drying (washing and drying steps).
[0168] <Various measurement methods, etc.>
[0169] Various measurement methods and the like are described below.
[0170] <Image of toner particle cross section obtained using scanning transmission electron microscope (STEM)>
[0171] The state of the wax in the toner particles is checked by observing the cross section of the toner particles with a scanning transmission electron microscope. The cross section observation of the toner particles is performed after ruthenium staining. In other words, the cross section image of the toner particles according to the present disclosure can be a cross section image of the toner particles stained with ruthenium.
[0172] The procedure of observing the cross section of toner is described below.
[0173] The toner dispersed as much as possible is embedded in a visible light curable resin (D-800, manufactured by NisshinEM Corporation), and cut into a thickness of 100 nm with an ultrasonic ultramicrotome (UC7, manufactured by Leica).
[0174] The thin-section sample thus prepared was stained for 15 minutes in a RuO4 atmosphere of 500 Pa using a vacuum staining device (VSC4R1H, manufactured by Filgen, Inc.), and a STEM image was obtained using a scanning transmission electron microscope (JEM2800, manufactured by JEOL Ltd.). Since the degree of staining of the crystalline wax and the resin is different under the staining conditions, the state of the wax can be checked from the contrast difference. The observation conditions include an accelerating voltage of 200 kV, a STEM probe size of 1 nm, an image size of 1024×1024 pixels, and a magnification of 30,000. A dark field (STEM-DF) image is obtained. The contrast and brightness are adjusted so that the portion mainly composed of the resin component has a maximum pixel value at a brightness of 150 in the brightness histogram of IMAGE J described later. In addition, the brightness of the wax in the cross section of the toner particle is adjusted to 0.
[0175] In this case, in order to select the toner particles for obtaining the cross-sectional image, after measuring the weight average particle size (D4) of the toner by the measurement method described later, 10 toner particles having a major axis diameter in the range of 0.8 to 1.1 times D4 are selected. The image is obtained so that there are no more than two toner particles in the field of view of the image.
[0176] <Brightness Histogram and Physical Properties Obtained from the Histogram>
[0177] The brightness histogram is created by analyzing the STEM image of the cross section of the toner particle obtained by the above method using the image processing software IMAGE J (developed by Wayne Rashand). Therefore, the brightness histogram can be created by measuring the brightness spectrum of 256 tones on the image obtained from the image analysis of the cross section of the toner particle. The specific steps are described below.
[0178] First, convert the backscattered electron image to be analyzed to 8-bit using the Type option in the Image menu.
[0179] Next, specify the area to be analyzed only within the outline of the toner. The outline of the toner is defined by the interface between the visible light curable resin and the toner cross section. Use Clear Outside from the Edit menu to delete the area outside the area to be analyzed.
[0180] Use Filters in the Process menu and set the Median Size to 2.0 pixels to reduce image noise.
[0181] Next, select Histogram from the Analyze menu to display the brightness histogram in a new window. The values of the brightness histogram are obtained from the List in the window. The following values are calculated from the values.
[0182] · Brightness width corresponding to 20% or more of the pixel value at brightness P in the brightness range of 10 to 245
[0183] Total pixel values C in the brightness range of 0 to 9 and total pixel values A in the brightness range of 0 to 245
[0184] When the pixel value in the brightness range of 10 to 245 in the histogram has a maximum value P at a brightness X of 140 or more and less than 160, the brightness of the STEM image can be adjusted using the motion image editing software Microsoft Photo (Microsoft Corporation). In such a case, the STEM image from which the area outside the area to be analyzed is deleted using IMAGE J is opened in advance using the motion image editing software Microsoft Photo. Select Edit from the Edit and Create menu, and move the cursor on the adjustment screen to adjust the brightness to a brightness X of 150.
[0185] The STEM image after brightness adjustment was opened again using IMAGE J, and the analysis area within the contour of the toner was selected to create a brightness histogram. The values of the brightness histogram were obtained from the list (List) of brightness histograms.
[0186] When the brightness P is not within the brightness range of 140 or more and less than 160, it is necessary to obtain a STEM image again so that the brightness P is 150.
[0187] The same image analysis was performed on 10 STEM images of each toner to calculate the above values. The average value of the 10 STEM images was used as the physical properties of each toner.
[0188] <Method for measuring the content of various monomer units in resin>
[0189] The content of various monomer units in the resin is determined by 1 H-NMR is measured under the following conditions.
[0190] Measuring equipment: FT NMR JNM-EX400 (manufactured by JEOL Ltd.)
[0191] Measuring frequency: 400MHz
[0192] Pulse condition: 5.0μs
[0193] Frequency range: 10,500Hz
[0194] Scan times: 64
[0195] Measuring temperature: 30℃
[0196] Sample: 50 mg of the sample was placed in a sample tube having an inner diameter of 5 mm. Tritiated chloroform (CDCl3) was added to the sample as a solvent and dissolved in a thermostat at 40°C to prepare a sample.
[0197] analyze 1 H-NMR chart to identify the structure of each monomer unit. The following describes the measurement of the content of monomer unit A in vinyl polymer A as an example. 1 In the H-NMR chart, a peak independent of peaks attributable to components of other monomer units is selected from the peaks attributable to the component of monomer unit A, and the integrated value S1 of the peak is calculated. For other monomer units in the vinyl polymer A, the integrated values are calculated in the same manner.
[0198] When the vinyl polymer A is composed of monomer unit A and other monomer units, the content of monomer unit A is determined from the integrated value S1 and the integrated value S2 of the peak of other monomer units as follows. n1 and n2 represent the number of hydrogen atoms in the component to which the peak of interest belongs.
[0199] Content of monomer unit A (mol%) = {(S1 / n1) / ((S1 / n1)+(S2 / n2))}×100
[0200] Even for two or more other monomer units, the content of the monomer unit A can be calculated in the same manner.
[0201] When a polymerizable monomer having no hydrogen atom other than a vinyl group is used, the measurement core is performed in a single pulse mode. 13 C's 13 C-NMR, and by 1 H-NMR was calculated in the same manner.
[0202] The ratio (mol %) of each unit calculated by the above method is multiplied by the molecular weight of each unit to convert the ratio of each unit into mass percentage.
[0203] In the NMR measurement of the toner, independent peaks are not observed due to the overlap between the peaks of the wax and the resin other than the vinyl polymer A. Therefore, it may not be possible to calculate the ratio of each unit in the vinyl polymer A. In such a case, the vinyl polymer A' is produced in the same manner without using the wax or other resins, and the vinyl polymer A' may be analyzed as the vinyl polymer A.
[0204] <Method for measuring weight average molecular weight (Mw) of resin>
[0205] The weight average molecular weight (Mw) of the resin is measured by gel permeation chromatography (GPC) as described below.
[0206] First, the sample was dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The solution was passed through a solvent-resistant membrane filter "Myshori Disk" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to prepare a sample solution. The sample solution was adjusted so that the concentration of the THF soluble component was 0.8% by mass. The sample solution was measured under the following conditions.
[0207] Equipment: HLC8120 GPC (detector: RI) (manufactured by Tosoh Corporation)
[0208] Column: Shodex KF-801, 802, 803, 804, 805, 806, and 807 series (manufactured by Showa Denko KK)
[0209] Eluent: Tetrahydrofuran (THF)
[0210] Flow rate: 1.0mL / min
[0211] Oven temperature: 40.0℃
[0212] Sample injection volume: 0.10mL
[0213] The molecular weight of the sample is calculated from a molecular weight calibration curve prepared using a standard polystyrene resin (e.g., trade name "TSK standard polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, and A-500", manufactured by Tosoh Corporation).
[0214] <Measurement of Molecular Weight of Wax>
[0215] The molecular weight of the release agent is measured by gel permeation chromatography (GPC) as follows: Special grade 2,6-di-tert-butyl-4-methylphenol (BHT) is dissolved in o-dichlorobenzene for gel chromatography at room temperature at a concentration of 0.10 mass% / volume.
[0216] The release agent and o-dichlorobenzene added with BHT were placed in a sample bottle and heated on a hot plate at 150°C to dissolve the release agent. After the release agent was dissolved, the sample bottle was placed in a preheated filter unit and placed in the body. The sample passed through the filter unit was used as a GPC sample. The sample solution was adjusted so that the concentration was 0.15% by mass. The sample solution was measured under the following conditions.
[0217] Equipment: HLC-8121GPC / HT (manufactured by Tosoh Corporation)
[0218] Detector: High temperature RI
[0219] Columns: Two TSKgel GMHHR-H HT (manufactured by Tosoh Corporation) column series
[0220] Temperature: 135.0℃
[0221] Solvent: o-dichlorobenzene for gel chromatography (containing 0.10 mass% / volume BHT)
[0222] Flow rate: 1.0mL / min
[0223] Injection volume: 0.4mL
[0224] The molecular weight of the releasing agent is calculated from a molecular weight calibration curve prepared using a standard polystyrene resin (e.g., trade names “TSK standard polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, and A-500”, manufactured by Tosoh Corporation).
[0225] <Method for measuring melting point>
[0226] The melting point was measured with DSC Q1000 (manufactured by TA Instruments) under the following conditions.
[0227] Heating rate: 10℃ / min
[0228] Starting temperature: 20℃
[0229] Final temperature: 180℃
[0230] The melting points of indium and zinc were used for temperature calibration of the detection cell, and the heat of fusion of indium was used for calorimetric calibration.
[0231] More specifically, 5 mg of the sample was accurately weighed and placed in an aluminum pan, and subjected to differential scanning calorimetry. An empty silver pan was used as a reference.
[0232] The melting point is defined as the peak temperature of the maximum endothermic peak in the first temperature rising process.
[0233] For multiple peaks, the maximum endothermic peak is the peak at which the amount of endothermic heat is the largest.
[0234] <Measurement of Weight Average Particle Diameter (D4) of Toner>
[0235] The weight average particle size (D4) of the toner is determined as follows. The measuring device is a precision particle size distribution analyzer "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.) equipped with a 100 μm orifice tube using a pore resistance method. The accompanying dedicated software "Beckman Coulter, Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.) is used to set the measurement conditions and analyze the measurement data. The number of effective measurement channels is 25,000.
[0236] The aqueous electrolyte solution used in the measurement may be 1% special grade sodium chloride dissolved in deionized water, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.).
[0237] Prior to measurement and analysis, the dedicated software was set up as follows.
[0238] In the "Standard Measurement Method (SOMME) Setup" screen of the dedicated software, set the total count in control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained with "Standard Particles 10.0 μm" (manufactured by Beckman Coulter, Inc.). Press the "Threshold / Noise Level Measurement Button" to automatically set the threshold and noise level. Set the current to 1600 μA. Set the gain to 2. Select Isoton II as the electrolyte solution. Check "Rinse the orifice tube after measurement".
[0239] In the "Pulse to Size Conversion" setting screen of the dedicated software, set the element spacing to logarithmic size, the size elements to 256 size elements, and the size range to 2 to 60 μm.
[0240] The specific measurement method is as follows.
[0241] (1) Place 200.0 mL of electrolyte aqueous solution in a 250 mL round-bottom glass beaker for Multisizer 3 and place it on the sample stage. Stir the stirring bar counterclockwise at 24 revolutions per second. Use the "aperture tube flushing" function of the dedicated software to remove dirt and bubbles in the aperture tube.
[0242] (2) 30.0 mL of an aqueous electrolyte solution was placed in a 100 mL flat-bottom glass beaker. 0.3 mL of a dispersant "Contaminon N" (a 10% by mass aqueous solution of a neutral detergent for precision measuring instruments composed of a nonionic surfactant, an anionic surfactant, and an organic builder, with a pH of 7, manufactured by Wako Pure Chemical Industries, Ltd.) was added to the aqueous electrolyte solution.
[0243] (3) An ultrasonic disperser "Ultrasonic Dispersion System Tetra 150" (manufactured by Nikkaki-Bios Co., Ltd.) was prepared. The ultrasonic disperser included two oscillators with an oscillation frequency of 50 kHz and the power output of the ultrasonic disperser was 120 W. The phase difference between the two oscillators was 180 degrees. 3.3 L of deionized water was charged into the water tank of the ultrasonic disperser, and 2.0 mL of Contaminon N was added to the deionized water.
[0244] (4) Place the beaker in (2) in the beaker fixing hole of the ultrasonic disperser and start the ultrasonic disperser. Adjust the vertical position of the beaker so that the surface resonance of the electrolyte aqueous solution in the beaker is maximized.
[0245] (5) While the electrolyte aqueous solution in the beaker in (4) is exposed to ultrasonic waves, 10 mg of the toner particles are added little by little to the electrolyte aqueous solution and dispersed. The ultrasonic dispersion treatment is continued for another 60 seconds. During the ultrasonic dispersion, the water temperature in the water tank is controlled within a temperature range of 10° C. to 40° C.
[0246] (6) The aqueous electrolyte solution containing dispersed toner particles prepared in (5) is dropped into the round bottom beaker prepared in (1) placed on the sample stage using a pipette so that the measurement concentration becomes 5%. The measurement is continued until the number of particles measured reaches 50,000.
[0247] (7) Analyze the measurement data using the attached dedicated software to determine the weight average particle size (D4). The "Average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen in the setting chart / volume % in the dedicated software is the weight average particle size (D4).
[0248] [Exemplary Embodiments]
[0249] Although the present disclosure is described in more detail in the following exemplary embodiments, the present disclosure is not limited to these exemplary embodiments. Unless otherwise specified, the "parts" in the following formulas are based on mass.
[0250] The measurement results in the exemplary embodiment are measured by the above-mentioned method. The 50% particle diameter (D50) based on the volume distribution of the dispersion liquid is measured with a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.).
[0251] <Production Example of Shell Resin>
[0252] The following materials were placed in an autoclave equipped with a decompression device, a water separator, a nitrogen introduction device, a temperature measuring device, and a stirrer.
[0253] · 32.3 parts by mass of terephthalic acid (50.0 mol%)
[0254] · Bisphenol A propylene oxide 2 mol adduct 67.7 parts by mass (50.0 mol%)
[0255] ·0.02 parts of potassium titanium oxalate
[0256] The reaction was carried out at 220°C for 8 hours under nitrogen atmosphere at normal pressure to obtain a non-crystalline polyester as a shell resin. The shell resin had a weight average molecular weight (hereinafter also referred to as Mw) of 20,000 and a glass transition temperature (Tg) of 70°C.
[0257] <Wax for Toner Production>
[0258] Table 1 shows the types and physical properties of waxes used in the production of toner.
[0259] Table 1
[0260] Types of wax Molecular weight Melting point[℃] Wax 1 Dipentaerythritol hexabehenate 2190 86 Wax 2 Dipentaerythritol hexastearate 1853 79 Wax 3 Dipentaerythritol hexapalmitate 1685 73 Wax 4 Tripentaerythrityl Octabehenate 2162 84 Wax 5 Pentaerythritol tetrabehenate 1426 76 Wax 6 Glyceryl Tribehenate 1059 68 Wax 7 Stearyl Stearate 537 62 Wax 8 Hydrocarbon wax (HNP51, Nippon Seiro Co., Ltd.) 469 78 Wax 9 Hydrocarbon wax (Excerex 30050B, Mitsui Chemicals, Inc.) 2700 91
[0261] <Production Example of Toner 1>
[0262] [Toner production by suspension polymerization]
[0263] Preparation of toner particles 1
[0264] The following materials were put into a grinder (manufactured by Nippon Coke & Engineering Co., Ltd.).
[0265] Methacrylonitrile (monomer (b)) 5.0 parts
[0266] Styrene (monomer (c)) 10.0 parts
[0267] · Ethyl methacrylate (monomer (d)) 15.0 parts
[0268] Colorant Pigment Blue 15:3 6.5 parts
[0269] These materials were dispersed with zirconia beads having a diameter of 5 mm at 200 rpm for 2 hours to prepare a raw material dispersion.
[0270] Separately, 735.0 parts of deionized water and 16.0 parts of trisodium phosphate 12 hydrate in a container equipped with a high-speed stirring homomixer (manufactured by Primix Corporation) and a thermometer are heated to 60°C under stirring at 12,000rpm. Subsequently, an aqueous solution of calcium chloride containing 9.0 parts of calcium chloride dihydrate dissolved in 65.0 parts of deionized water is poured into the container. The mixture is stirred at 12,000rpm for 30 minutes at 60°C. The pH of the mixture is adjusted to 6.0 with 10% hydrochloric acid. Therefore, an aqueous medium in which a dispersion stabilizer comprising hydroxyapatite is dispersed in water is prepared.
[0271] Then, the raw material dispersion liquid was transferred to a container equipped with a stirrer and a thermometer, and heated to 60° C. with stirring at 100 rpm. The following materials were added to the raw material dispersion liquid.
[0272] · Behenyl acrylate (monomer (a)) 50.0 parts
[0273] · Shell resin 4.0 parts
[0274] ·Wax 1 9.0 parts
[0275] After stirring at 100 rpm for 30 minutes at 60° C., 5.0 parts of a polymerization initiator, tert-butyl peroxypivalate (manufactured by NOF Corporation: Perbutyl PV) was added to the dispersion. The dispersion was stirred for one minute and poured into an aqueous medium stirred at 12,000 rpm with a high-speed stirrer. Stirring was continued at 12,000 rpm at 60° C. for 20 minutes with a high-speed stirrer to prepare a granulation liquid.
[0276] The granulation liquid was transferred to a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, a nitrogen inlet tube, and heated to 70° C. with stirring at 150 rpm in a nitrogen atmosphere. A polymerization reaction was performed at 70° C. at 150 rpm for 12 hours to prepare a toner particle dispersion liquid.
[0277] The toner particle dispersion was heated to 95° C., stirred at 95° C. at 150 rpm for 1 hour, cooled to 70° C. under stirring, and heat-treated at 70° C. for 3 hours. After the heat treatment, the toner particle dispersion was cooled to 30° C. The pH of the toner particle dispersion was adjusted to 1.5 with dilute hydrochloric acid under stirring to dissolve the dispersion stabilizer. Subsequently, the solid component was filtered out, fully washed with deionized water, and dried under vacuum at 30° C. for 24 hours to prepare toner particles 1 containing polymer A1.
[0278] 100.0 parts of Toner Particles 1 and 2.0 parts of external additive silica fine particles (hydrophobically treated with hexamethyldisilazane, number average particle diameter of primary particles: 10 nm) were mixed in an FM mixer (manufactured by Nippon Coke & Engineering Co., Ltd.) at 3000 rpm for 15 minutes to prepare Toner 1. Figure 1 One of ten brightness histograms of 256 tones obtained from the STEM image of the cross section of Toner 1 is shown. Figure 1 , the lightness X is 150, P is 7336, the lightness M is 215, and the lightness N is 30. Table 5 and Table 6 show the physical properties of Toner 1.
[0279] <Production Example of Toners 2 to 20 and 27 to 38>
[0280] Toners 2 to 20 and 27 to 38 were prepared in the same manner as in the production example of toner 1, except that the kind and addition amount of the monomer used were changed as shown in Table 2, and the kind and addition amount of the wax and the temperature and time of the heat treatment were changed as shown in Table 3. Tables 5 and 6 show the physical properties of toners 2 to 20 and 27 to 38.
[0281] Figure 2 One of ten brightness histograms of 256 tones obtained from the STEM image of the cross section of the toner 35 is shown. Figure 2 , the brightness X is 150, P is 15,709, the brightness M is 179, and the brightness N is 120.
[0282] Table 2
[0283]
[0284] The abbreviations in Table 2 are as follows:
[0285] BEA: Behenyl Acrylate
[0286] STA: Stearyl Acrylate
[0287] OCA: Dioctadecyl acrylate
[0288] MYA: Triacontyl acrylate
[0289] CEA: Cetyl Acrylate
[0290] MN: Methacrylonitrile VA: Vinyl acetate St: Styrene
[0291] VBA: Vinyl benzoate ME: Ethyl methacrylate AB: Butyl acrylate
[0292] Table 3
[0293]
[0294] In Table 3, Toners 14 and 38 were not heat treated.
[0295] <Production Example of Toner 21>
[0296] Production Example of Polymer A2
[0297] In a nitrogen atmosphere, the following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube.
[0298] · Toluene 100.0 parts by mass
[0299] · Monomer composition 100.0 parts by mass
[0300] The monomer composition was prepared by mixing behenyl acrylate, methacrylonitrile, ethyl methacrylate, and styrene in the following ratio.
[0301] Behenyl acrylate (monomer (a)) 50.0 parts by mass
[0302] · Methacrylonitrile 25.0 parts by mass
[0303] · Ethyl methacrylate 15.0 parts by mass
[0304] · Styrene 10.0 parts by mass
[0305] · tert-Butyl peroxypivalate (manufactured by NOF Corporation: Perbutyl PV) 0.5 parts
[0306] The reaction vessel was heated to 70° C. under stirring at 200 rpm to perform polymerization reaction for 12 hours, thereby preparing a solution in which the polymer of the monomer composition was dissolved in toluene. Then, the solution was cooled to 25° C. and 1000.0 parts of methanol were poured under stirring to precipitate the methanol insoluble matter. The methanol insoluble matter was filtered out, washed with methanol, and dried under vacuum at 40° C. for 24 hours to prepare polymer A2.
[0307] [Toner production by pulverization method]
[0308] Polymer A2 100.0 parts by mass
[0309] Colorant Pigment Blue 15:3 (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.) 6.5 parts by mass
[0310] Wax 1 9.0 parts by mass
[0311] Charge control agent (LR147: manufactured by Japan Carlit Co., Ltd.) 2.0 parts by mass
[0312] These materials were premixed in an FM mixer (manufactured by Nippon Coke & Engineering Co., Ltd.) and then melt-kneaded using a twin-screw extruder (PCM-30, manufactured by Ikegai Corporation) at a temperature of 120° C. and at a discharge temperature of 135° C. to prepare a kneaded product.
[0313] While the kneaded product was cooled, heat treatment was performed by keeping the kneaded product at 95° C. for 1 hour and then at 70° C. for 3 hours. The kneaded product after the heat treatment was coarsely ground with a hammer mill and then pulverized with a mechanical grinder (T-250, manufactured by Turbo Kogyo Co., Ltd.) to prepare pulverized powder. The pulverized powder was classified with a multi-stage classifier utilizing the Coanda effect to prepare toner particles 21 having a weight average particle size (D4) of 7.0 μm.
[0314] 100.0 parts of Toner Particles 21 were mixed with 2.0 parts of external additive silica fine particles (hydrophobically treated with hexamethyldisilazane, primary particle number average particle size: 10 nm) in an FM mixer (manufactured by Nippon Coke & Engineering Co., Ltd.) at 3000 rpm for 15 minutes to prepare Toner 21. Tables 5 and 6 show the physical properties of Toner 21.
[0315] <Production Example of Toner 22>
[0316] [Toner production by emulsion aggregation method]
[0317] Preparation of polymer A2 dispersion
[0318] ·Toluene 300.0 parts by mass
[0319] Polymer A2 100.0 parts by mass
[0320] These materials were weighed and mixed, and the polymer A2 was dissolved at 90° C. to prepare a toluene solution.
[0321] Separately, 5.0 parts by mass of sodium dodecylbenzene sulfonate and 10.0 parts by mass of sodium laurate are added to 700.0 parts by mass of deionized water, and dissolved by heating at 90°C to prepare an aqueous solution. Then, the toluene solution and the aqueous solution are mixed, and stirred at 7000rpm with an ultra-high-speed stirrer TK Robomix (manufactured by Primix Corporation). Further, emulsification is performed under a pressure of 200MPa with a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Co., Ltd.). Toluene is then removed with an evaporator, and the concentration is adjusted with deionized water to prepare a polymer A2 dispersion liquid containing fine particles of 20% by mass of polymer A2.
[0322] The 50% particle size (D50) based on volume distribution of the polymer A2 dispersion was 0.40 μm.
[0323] Preparation of wax dispersion 1
[0324] Wax 1 100.0 parts by mass
[0325] Anionic surfactant Neogen RK (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) 5.0 parts by mass
[0326] · Deionized water 395.0 parts by mass
[0327] These materials were heated to 90° C. in a mixing container equipped with a stirrer. The materials were circulated to Clearmix W-motion (manufactured by M Technique Co., Ltd.) for dispersion treatment for 60 minutes. The conditions for the dispersion treatment were as follows:
[0328] Rotor outer diameter: 3cm
[0329] Gap: 0.3mm
[0330] Rotor speed: 19,000rpm
[0331] Screen speed: 19,000rpm
[0332] After the dispersion treatment, the material was cooled to 40° C. under cooling conditions of a rotor rotation speed of 1000 rpm, a screen rotation speed of 0 rpm, and a cooling rate of 10° C. / min to prepare a wax dispersion 1 containing fine particles of Wax 1 at 20% by mass.
[0333] The 50% particle size (D50) based on volume distribution of fine particles of Wax 1 was 0.15 μm.
[0334] Preparation of colorant dispersion 1
[0335] Colorant (Pigment Blue 15:3) 50.0 parts by mass
[0336] Anionic surfactant Neogen RK (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) 7.5 parts by mass
[0337] ·442.5 parts by mass of deionized water
[0338] These materials are weighed, mixed, dissolved, and dispersed with a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Co., Ltd.) for 1 hour to prepare a colorant dispersion liquid 1 containing 10% by mass of fine particles of the colorant.
[0339] The 50% particle size (D50) of the fine particles of the colorant based on volume distribution was 0.20 μm.
[0340] Preparation of Toner 22
[0341] Combine the following materials in a round stainless steel flask.
[0342] 500.0 parts by mass of polymer A2 dispersion
[0343] Wax dispersion 1 45.0 parts by mass
[0344] Colorant dispersion 1 80.0 parts by mass
[0345] · Deionized water 160.0 parts by mass
[0346] The mixture was dispersed at 5000 rpm for 10 minutes with a homogenizer Ultra-Turrax T50 (manufactured by IKA). The pH of the mixture was adjusted to 3.0 with a 1.0% nitric acid aqueous solution. The mixture was heated to 58° C. in a heating water bath while appropriately adjusting the rotation speed when the mixture was stirred with a stirring blade. When aggregates having a weight-average particle size (D4) of 6.0 μm were formed, the pH of the mixture was adjusted to 9.0 with a 5% sodium hydroxide aqueous solution. Then, the mixture was heated to 75° C. under stirring. The aggregates were fused by keeping at 75° C. for 1 hour.
[0347] Subsequently, the temperature was raised to 90° C., then, maintained at 90° C. for 1 hour and then maintained at 70° C. for 3 hours to perform heat treatment.
[0348] After the heat treatment, the mixture was cooled to 30° C., filtered, solid-liquid separated, and washed with deionized water. After washing, the mixture was dried with a vacuum dryer to prepare toner particles 22 having a weight average particle size (D4) of 6.1 μm.
[0349] 100.0 parts of Toner Particles 22 were mixed with 2.0 parts of external additive silica fine particles (hydrophobically treated with hexamethyldisilazane, primary particle number average particle size: 10 nm) in an FM mixer (manufactured by Nippon Coke & Engineering Co., Ltd.) at 3000 rpm for 15 minutes to prepare Toner 22. Tables 5 and 6 show the physical properties of Toner 22.
[0350] <Production Example of Toner 23>
[0351] [Toner production by the solution suspension method]
[0352] Preparation of Colorant Dispersion 2
[0353] Place the following ingredients into a heat-resistant glass container.
[0354] Colorant (Pigment Blue 15:3) 100.0 parts by mass
[0355] 150.0 parts by mass of ethyl acetate
[0356] Glass beads (1 mm) 200.0 parts by mass
[0357] After dispersion for 5 hours with a paint shaker, the glass beads were removed with a nylon sieve to prepare Colorant Dispersion Liquid 2. The 50% particle size (D50) based on volume distribution of Colorant Dispersion Liquid 2 was 0.20 μm.
[0358] Preparation of wax dispersion 2
[0359] Wax 1 20.0 parts by mass
[0360] 80.0 parts by mass of ethyl acetate
[0361] These materials in the sealable reaction vessel were heated at 80° C. with stirring. Subsequently, the system was cooled to 25° C. over 3 hours with slow stirring at 50 rpm to prepare a milky white liquid.
[0362] This liquid was put into a heat-resistant container together with 30.0 parts by mass of glass beads having a diameter of 1 mm, and dispersed for 3 hours in a paint shaker (manufactured by Toyo Seiki Seisaku-Sho, Ltd.). The glass beads were removed with a nylon sieve to prepare a wax dispersion 2. The 50% particle size (D50) based on volume distribution of the wax dispersion 2 was 0.23 μm.
[0363] Preparation of oil phase
[0364] The following materials in a beaker were stirred with a disperser (manufactured by Tokushu Kika Kogyo Co., Ltd.) at 3000 rpm for 1 minute.
[0365] Polymer A2 100.0 parts by mass
[0366] 85.0 parts by mass of ethyl acetate
[0367] The following materials were added to a beaker and stirred with a disperser (manufactured by Tokushu Kika Kogyo Co., Ltd.) at 6000 rpm for 3 minutes to prepare an oil phase.
[0368] Wax dispersion 2 (solid content: 20% by mass) 45.0 parts by mass
[0369] Colorant dispersion 2 (solid content: 40% by mass) 12.5 parts by mass
[0370] 5.0 parts by mass of ethyl acetate
[0371] Preparation of aqueous phase
[0372] · Sodium dodecyl diphenyl ether disulfonate aqueous solution (Eleminol MON7, manufactured by Sanyo Chemical Industries, Ltd.) 100.0 parts by mass
[0373] · Deionized water 900.0 parts by mass
[0374] The following materials in a beaker were stirred with a disperser (manufactured by Tokushu Kika Kogyo Co., Ltd.) at 3000 rpm for 3 minutes to prepare an aqueous phase.
[0375] Preparation of Toner 23
[0376] The oil phase is added to the aqueous phase and dispersed at 10,000 rpm for 10 minutes with a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.). The solvent is removed at 30° C. under a reduced pressure of 50 mmHg for 30 minutes. The resulting slurry is heated and stirred at 90° C. for 1 hour. Then, the slurry is cooled to 70° C. and heat-treated at 70° C. for 3 hours. After filtering, it is filtered out and redispersed in deionized water five times to remove the surfactant and form a filter cake.
[0377] The filter cake was dried under vacuum and then air-classified to prepare toner particles 23 .
[0378] External addition of toner particles 23 was performed in the same manner as in Toner 1 to prepare Toner 23. Tables 5 and 6 show the physical properties of Toner 23.
[0379] <Production Example of Toners 24 to 26>
[0380] Preparation of non-crystalline resin 1
[0381] While nitrogen gas was introduced into a heat-dried two-necked flask, the following materials were placed in the flask.
[0382] · Polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane 30.0 parts by mass
[0383] · Polyoxyethylene (2.2)-2,2-bis(4-hydroxyphenyl)propane 33.0 parts by mass
[0384] · 21.0 parts by mass of terephthalic acid
[0385] · 15.0 parts by mass of dodecenylsuccinic acid
[0386] · Dibutyltin oxide 0.1 parts by mass
[0387] The system was purged with nitrogen and stirred at 215° C. for 5 hours. Then, the temperature was gradually raised to 230° C. under reduced pressure with stirring, and maintained for another 2 hours. Subsequently, the reaction was stopped by air cooling to prepare a non-crystalline polyester as non-crystalline resin 1. The weight average molecular weight (Mw) of non-crystalline resin 1 was 23,500 and the glass transition temperature (Tg) was 55° C.
[0388] Preparation of non-crystalline resin dispersion 1
[0389] The following materials were mixed and dissolved at 90°C.
[0390] ·Toluene 300.0 parts by mass
[0391] Non-crystalline resin 1 100.0 parts by mass
[0392] Separately, the following materials were mixed and dissolved at 90°C.
[0393] · 700.0 parts by mass of deionized water
[0394] 5.0 parts by mass of sodium dodecylbenzene sulfonate
[0395] · Sodium laurate 10.0 parts by mass
[0396] The obtained aqueous solution and toluene solution were mixed and stirred at 7000 rpm with an ultra-high speed stirrer TK Robomix (manufactured by Primix Corporation). Further, emulsification was performed under a reduced pressure of 200 MPa with a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Co., Ltd.). Toluene was then removed with an evaporator, and the concentration was adjusted with deionized water to prepare a non-crystalline resin 1 dispersion containing 20% by mass of fine particles of non-crystalline resin 1.
[0397] The 50% particle size (D50) based on volume distribution of the non-crystalline resin fine particles was 0.38 μm.
[0398] [Toner production by emulsion aggregation method]
[0399] Toners 24 to 26 were prepared in the same manner as in Production Example of Toner 22 except that the addition amount of the polymer A2 dispersion and the addition amount of the non-crystalline resin dispersion 1 were changed as shown in Table 4. Tables 5 and 6 show the physical properties of Toners 24 to 26.
[0400] Table 4
[0401]
[0402] <Production Example of Toner 39>
[0403] Preparation of polymer A3
[0404] Under a nitrogen atmosphere, the following materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube.
[0405] · Toluene 100 parts by mass
[0406] · 1 part by mass of dodecanethiol
[0407] · Monomer composition 100 parts by mass
[0408] The monomer composition was prepared by mixing behenyl acrylate and acrylic acid in the following ratio.
[0409] Behenyl acrylate (monomer (a)) 91.5 parts by mass
[0410] 8.5 parts by mass of acrylic acid
[0411] · Azoisobutyronitrile (AIBN) 0.75 parts by mass
[0412] The reaction vessel was heated to 70° C. under stirring at 200 rpm to perform polymerization reaction for 16 hours, thereby preparing a solution in which the polymer of the monomer composition was dissolved in toluene. Then, the solution was cooled to 25° C. and 1000.0 parts of methanol were poured under stirring to precipitate the methanol insoluble matter. The methanol insoluble matter was filtered out, washed with methanol, and dried under vacuum at 40° C. for 24 hours to prepare polymer A3.
[0413] Preparation of polymer A3 dispersion
[0414] Polymer A3 30 parts by mass
[0415] · 1.5 parts by mass of sodium dodecylbenzene sulfonate
[0416] · 150 parts by weight of deionized water
[0417] These materials were weighed, mixed, heated to 90°C, and stirred at 8000 rpm with a homogenizer (Ultra-Turrax T50, manufactured by IKA) to prepare a polymer A3 dispersion liquid. The 50% particle size (D50) based on volume distribution of the polymer A3 dispersion liquid was 0.30 μm.
[0418] Preparation of non-crystalline resin 2
[0419] While nitrogen gas was introduced into a heat-dried two-necked flask, the following materials were placed in the flask.
[0420] · Polyoxyethylene (2,2)-2,2-bis(4-hydroxyphenyl)propane 19.0 parts by mass
[0421] · Polyoxypropylene (2,2)-2,2-bis(4-hydroxyphenyl)propane 51.0 parts by mass
[0422] · 23.0 parts by mass of terephthalic acid
[0423] · 4.5 parts by mass of n-dodecenylsuccinic acid
[0424] · 3.0 parts by mass of isophthalic acid
[0425] · Dibutyltin oxide 0.02 parts by mass
[0426] The system was purged with nitrogen and heated to react for about 12 hours in a temperature range of 150° C. to 230° C. Subsequently, the pressure was gradually reduced in a temperature range of 210° C. to 250° C. to prepare non-crystalline resin 2. The non-crystalline resin 2 had a weight average molecular weight (Mw) of 15,400 and a glass transition temperature (Tg) of 65° C.
[0427] Preparation of non-crystalline resin 2 dispersion
[0428] Non-crystalline resin 2 30 parts by mass
[0429] 100 parts by mass of ethyl acetate
[0430] These materials are weighed and mixed to dissolve the non-crystalline resin 2. Further, the following materials are added.
[0431] · 1.5 parts by mass of sodium dodecylbenzene sulfonate
[0432] ·Deionized water 150g
[0433] The mixture was heated to 60° C. and stirred at 8000 rpm with a homogenizer (Ultra-Turrax T50, manufactured by IKA). Then, ethyl acetate was evaporated to prepare a non-crystalline resin 2 dispersion. The 50% particle size (D50) based on volume distribution of the non-crystalline resin 2 dispersion was 0.18 μm.
[0434] Preparation of colorant dispersion 3
[0435] Colorant (Pigment Blue 15:3) 50 parts by mass
[0436] Anionic surfactant Neogen SC (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) 5.0 parts by mass
[0437] ·200.0 parts by mass of deionized water
[0438] These materials were mixed, dissolved, and dispersed with a homogenizer (Ultra-Turrax, manufactured by IKA) for 10 minutes to prepare a colorant dispersion liquid 3 having a central particle diameter of 175 nm and a solid content of 22.5 parts by mass.
[0439] Preparation of wax dispersion 3
[0440] Wax 7 25.0 parts by mass
[0441] Anionic surfactant Neogen SC (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) 5.0 parts by mass
[0442] ·200.0 parts by mass of deionized water
[0443] These materials were mixed, heated to 97°C, and then dispersed with a homogenizer (Ultra-Turrax T50, manufactured by IKA). 2A dispersion treatment was performed 20 times with a Gaulin homogenizer (manufactured by Meiwa Shoji) to prepare a wax dispersion 3. The 50% particle size (D50) based on volume distribution of the wax dispersion 3 was 0.20 μm.
[0444] Preparation of Toner 39
[0445] · 400.0 parts by mass of non-crystalline resin 2 dispersion
[0446] · 100.0 parts by mass of polymer A3 dispersion
[0447] Colorant dispersion 3 20.0 parts by mass
[0448] Wax dispersion 3 70.0 parts by mass
[0449] 1.5 parts by mass of a 10% by mass aqueous solution of poly(aluminum chloride) (manufactured by Asada Chemical Industry Co., Ltd.)
[0450] These materials were mixed and dispersed in a round stainless steel flask with a homogenizer (Ultra-Turrax T50, manufactured by IKA), heated to 45°C with stirring, and maintained at 45°C for 30 minutes.
[0451] Subsequently, the temperature of the contents was gradually raised to 55° C., and a sodium hydroxide aqueous solution was added to adjust the pH to 8. Then, the temperature was raised to 90° C. to allow the aggregates to coalesce for 1 hour. Thus, after cooling and filtering, the toner particles 39 were washed with deionized water and dried.
[0452] 100.0 parts of Toner Particles 39 were mixed with 2.0 parts of external additive silica fine particles (hydrophobically treated with hexamethyldisilazane, primary particle number average particle diameter: 10 nm) in an FM mixer (manufactured by Nippon Coke & Engineering Co., Ltd.) at 3000 rpm for 15 minutes to prepare Toner 39. Tables 5 and 6 show the physical properties of Toner 39.
[0453] Table 5
[0454]
[0455] * Toner 27: 7.0 parts Wax 1 and 2.0 parts Wax 9 Toner 28: 2.0 parts Wax 1 and 7.0 parts Wax 9
[0456] Toner 29: 5.0 parts Wax 1 and 4.0 parts Wax 9
[0457] Toner 30: 4.0 parts wax 1 and 5.0 parts wax 9
[0458] In Table 5, Wc of the ester wax refers to the average number of carbon atoms in the linear alkyl group in the ester wax.
[0459] In Table 5, the melting point and Mw of polymer A are those produced in the same manner as in the production example of the corresponding toner, except that the shell resin, wax, and colorant were not added, and the mixing step with silica fine particles was not performed.
[0460] Since the polymer thus produced is produced in the same manner as the resin contained in the corresponding toner, it is judged that the polymer has the same physical properties as the polymer A contained in the toner.
[0461] Table 6
[0462] |Ac-Wc| Brightness M-Brightness N C / A Melting point [℃] Weight average particle size D4 (μm) Toner 1 1.0 172 0.010 62 6.1 Toner 2 1.0 171 0.011 54 6.2 Toner 3 7.0 129 0.039 77 5.9 Toner 4 9.0 121 0.044 76 5.9 Toner 5 5.0 163 0.025 61 6.0 Toner 6 3.0 168 0.022 55 6.2 Toner 7 1.0 123 0.002 60 5.8 Toner 8 1.0 160 0.004 61 5.8 Toner 9 1.0 182 0.024 64 6.3 Toner 10 1.0 121 0.002 62 5.8 Toner 11 1.0 129 0.003 62 5.8 Toner 12 1.0 193 0.034 63 6.3 Toner 13 1.0 198 0.081 63 6.4 Toner 14 1.0 125 0.023 63 6.4 Toner 15 1.0 141 0.004 62 6.2 Toner 16 1.0 152 0.007 63 6.1 Toner 17 1.0 121 0.080 55 5.5 Toner 18 1.0 135 0.071 55 5.6 Toner 19 1.0 182 0.008 63 6.3 Toner 20 1.0 190 0.009 64 6.3 Toner 21 1.0 173 0.009 64 7.0 Toner 22 1.0 172 0.008 62 6.3 Toner 23 1.0 172 0.012 64 6.3 Toner 24 1.0 126 0.066 56 5.9 Toner 25 1.0 128 0.062 56 6.0 Toner 26 1.0 154 0.029 61 6.1 Toner 27 1.0 / - 167 0.016 62 6.1 Toner 28 1.0 / - 123 0.110 65 6.1 Toner 29 1.0 / - 148 0.078 63 6.2 Toner 30 1.0 / - 139 0.083 63 6.1 Toner 31 1.0 167 0.011 64 5.9 Toner 32 1.0 149 0.013 59 5.8 Toner 33 1.0 165 0.009 61 6.1 Toner 34 1.0 161 0.010 59 6.0 Toner 35 - 75 0.145 62 5.8 Toner 36 7.0 98 0.122 64 5.9 Toner 37 1.0 131 0.011 51 6.4 Toner 38 7.0 77 0.105 64 6.0 Toner 39 5.0 85 0.136 66 6.4
[0463] <Exemplary embodiment 1>
[0464] Toner 1 was examined as follows. Table 7 shows the evaluation results. <Evaluation of Low-Temperature Fixability of Toner>
[0465] A laser beam printer (trade name: LBP-7700C, manufactured by CANON KABUSHIKI KAISHA) was modified to be used as an image forming apparatus for evaluating the low temperature fixability of a toner. The printer was modified so that it could be operated without a fixing unit and the fixing temperature could be freely set. The image was output on white paper (trade name: Fox River Bond (90 g / m 2 ), FOX RIVER).
[0466] First, take out the toner from the box, and clean the box by blowing. Then, fill the box with 300g of toner 1. The box is placed at a temperature of 25°C and a humidity of 40%RH for 48 hours, and then installed in the cyan station of the printer at the same temperature and humidity. A dummy box is installed in the other station. Evaluation is performed under the same environment as described above.
[0467] Subsequently, an unfixed image of the image pattern was output on paper using an image forming apparatus without a fixing unit. The image pattern was a 10 mm × 10 mm square image transferred to 9 intersections that divided the long and short sides of the paper into four equal parts. The toner load on the paper was 0.80 mg / cm 2 .
[0468] The unfixed image was fixed with the removed fixing unit at a process speed of 250 mm / s and an initial temperature of 90° C. The temperature was raised at intervals of 5° C. to form a fixed image at each temperature. A lens cleaning paper ["Dasper(R)" (Ozu Paper Co., Ltd.)] at 50 g / cm 2 The image was fixed by friction with a load of . The image density was measured before and after friction. The low temperature fixability of the toner was evaluated based on the initial fixing temperature at which the image density after friction reached 20% or less of the image density before friction. An initial fixing temperature of 120° C. or less was judged to have the advantages of the present disclosure. Table 7 shows the evaluation results.
[0469] <Evaluation of Toner Durability>
[0470] The releasability of the toner was evaluated under a normal temperature and humidity environment, i.e., at a temperature of 25° C. and a humidity of 40% RH, using a modified image forming apparatus and paper used in the evaluation of low temperature fixability. The durability of the toner was evaluated based on the contamination concentration of the non-image area due to fine powder formed by cracking or breaking of the toner.
[0471] First, a full white image was output on an evaluation paper with a sticky note attached to the lower center at a processing speed of 120 mm / s. The contamination concentration Di (%) of the non-image area before the durability test was the difference between the reflectivity D1 (%) of the part of the evaluation paper covered by the sticky note and the reflectivity D2 (%) of the uncovered part (Di = D2-D1 (%)). The reflectivity was measured using a "Reflectometer Model TC-6DS (manufactured by Tokyo Denshoku Co., Ltd.)" equipped with an amber filter.
[0472] Next, a horizontal line pattern with a printing rate of 1% was output on two sheets of paper during one job. The printer was temporarily stopped before the next job. A total of 15,000 images were output in this mode. The printer was turned off and left for 72 hours immediately after the image output was completed. Then, the printer was turned on again. A full white image was output on an evaluation paper with a sticky note attached to the lower center, and the contamination concentration (Dr (%)) of the non-image area after the durability test was calculated as described above.
[0473] The durability of the toner was evaluated based on (Dr-Di) calculated from the two values. The evaluation results are shown in Table 7. A value of (Dr-Di) of less than 4.0% was judged to have the advantages of the present disclosure.
[0474] <Evaluation of Releasability of Toner>
[0475] The toner releasability was evaluated using a modified image forming apparatus used in the evaluation of low temperature fixability. White paper (trade name: GF-500 (A4, basis weight: 64.0 g / m 2 , Canon Marketing Japan Inc.). The cartridge was filled with 300 g of Toner 1 as described above.
[0476] Using a modified printer without a fixing unit, an unfixed image with a width of 100 mm in the paper passing direction and a width of 200 mm in the direction perpendicular to the paper passing direction was output on the evaluation paper with a space of 1 mm from the edge of the evaluation paper. The paper passing direction was the length direction, and the toner load of the unfixed image was 0.8 mg / cm 2 .
[0477] The toner releasability was evaluated with the taken out fixing unit according to the number of temperatures at which the fixed image did not wrap around the fixing roller while the temperature was raised 6 times at intervals of 10° C. from the initial fixing temperature set for the evaluation of low temperature fixability. Table 7 shows the evaluation results. At least one temperature at which the fixed image did not wrap around the fixing roller was judged to have the advantages of the present disclosure.
[0478] <Evaluation of High-temperature Storage Stability of Toner>
[0479] After 6 g of Toner 1 in a 100 mL polymer cup was left at a temperature of 50° C. and a humidity of 20% RH for 10 days, the cohesion degree of Toner 1 was measured as described below.
[0480] The measuring device is a digital display type vibration meter "Digi-Vibro MODEL 1332A" (manufactured by Showa Sokki Corporation) connected to the measuring surface of the vibration table of "Powder Tester" (manufactured by Hosokawa Micron Corporation). A sieve with an opening of 38 μm (400 mesh), a sieve with an opening of 75 μm (200 mesh), and a sieve with an opening of 150 μm (100 mesh) are stacked in sequence on the vibration table of Powder Tester. The measurement is carried out at 23° C. and 60% RH as described below.
[0481] (1) The vibration amplitude of the vibration table is pre-adjusted so that the displacement of the digital display vibration meter is 0.60 mm (peak-to-peak).
[0482] (2) The toner left for 10 days as described above is left at 23° C. and 60% RH for 24 hours. Then, 5 g of the toner is accurately weighed and gently placed on the uppermost sieve having an opening of 150 μm.
[0483] (3) After vibrating the sieve for 15 seconds, the mass of the toner remaining on each sieve was measured, and the cohesion degree (%) was calculated using the following formula. The evaluation results are shown in Table 7. A cohesion degree of 30% or less was judged to have the advantages of the present disclosure.
[0484] Cohesion (%) = {(mass of toner on a sieve with an opening of 150 μm (g)) / 5 (g)}×100
[0485] + {(mass of toner on the sieve with an opening of 75 μm (g)) / 5 (g)}×100×0.6
[0486] + {(mass of toner on the sieve with an opening of 38 μm (g)) / 5 (g)}×100×0.2
[0487] Table 7
[0488]
[0489] While the present disclosure has been described with reference to exemplary embodiments, it is to be understood that the present disclosure is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. A toner comprising toner particles containing a resin component and a wax, characterized in that: The resin component comprises a vinyl polymer A having a monomer unit A represented by formula (A): Where R 1 represents H or CH3, and R 2 represents a straight-chain alkyl group having 18 to 36 carbon atoms, The wax is an ester wax, The ester wax is an ester of alcohol and aliphatic monocarboxylic acid, and The monomer unit A consists of R 2 The number of carbon atoms Ac in the linear alkyl group represented by and the average number of carbon atoms Wc in the linear alkyl group contained in the ester wax satisfy the formula (5): |Ac-Wc|≤6.0 (5), in scanning transmission electron microscope observation of a cross section of the toner particle, obtaining a backscattered electron image of the cross section of the toner particle, assigning the brightness of each pixel constituting the backscattered electron image to one of 256 tones within a brightness range of 0 to 255, and creating a brightness histogram in which the horizontal axis represents brightness and the vertical axis represents pixel value, The total pixel value C in the brightness range of 0 to 9 and the total pixel value A in the brightness range of 0 to 245 satisfy equation (1): 0.000≤C / A≤0.250 (1) And when the pixel value in the brightness range of 10 to 245 in the histogram has a maximum value P at brightness X, the range of brightness M-brightness N is 120 to 235, wherein the brightness M represents the brightness at which the pixel value is lower than 20% of the maximum value P for the first time from the brightness X to brightness 245, and the brightness N represents the brightness at which the pixel value is lower than 20% of the maximum value P for the first time from the brightness X to brightness 10.
2. The toner according to claim 1, wherein C and A satisfy the formula (2): 0.000≤C / A≤0.100 (2). 3 . The toner according to claim 1 , wherein the content of the monomer unit A in the vinyl polymer A ranges from 20.0% by mass to 80.0% by mass. 4 . The toner according to claim 1 , wherein the content of the vinyl polymer A in the resin component is 30.0% by mass or more.
5. The toner according to claim 1, wherein The wax is an ester wax, and The ester wax is an ester of a trivalent or higher alcohol and an aliphatic monovalent carboxylic acid. The toner according to claim 5 , wherein the toner particles further contain a hydrocarbon-based wax. 7 . The toner according to claim 1 , wherein a mass ratio of the wax to the resin component ranges from 1.0% by mass to 25.0% by mass. 8 . The toner according to claim 1 , wherein the content of the vinyl polymer A in the resin component is 60% by mass or more.
9. A method for producing a toner, characterized in that: It includes the following steps: producing toner base particles comprising a wax and a resin component; and toner particles are produced by heat-treating the toner base particles at a temperature range of TmA to TmW for 30 minutes or more, wherein TmW represents the melting point of the wax, and TmA represents the melting point of the vinyl polymer A, and The toner includes toner particles containing a resin component and a wax, wherein The resin component comprises a vinyl polymer A having a monomer unit A represented by formula (A): Where R 1 represents H or CH3, and R 2 represents a straight-chain alkyl group having 18 to 36 carbon atoms, The wax is an ester wax, The ester wax is an ester of alcohol and aliphatic monocarboxylic acid, and The monomer unit A consists of R 2 The number of carbon atoms Ac in the linear alkyl group represented by and the average number of carbon atoms Wc in the linear alkyl group contained in the ester wax satisfy the formula (5): |Ac-Wc|≤6.0 (5), in scanning transmission electron microscope observation of a cross section of the toner particle, obtaining a backscattered electron image of the cross section of the toner particle, assigning the brightness of each pixel constituting the backscattered electron image to one of 256 tones within a brightness range of 0 to 255, and creating a brightness histogram in which the horizontal axis represents brightness and the vertical axis represents pixel value, The total pixel value C in the brightness range of 0 to 9 and the total pixel value A in the brightness range of 0 to 245 satisfy equation (1): 0.000≤C / A≤0.250 (1) And when the pixel value in the brightness range of 10 to 245 in the histogram has a maximum value P at brightness X, the range of brightness M-brightness N is 120 to 235, wherein the brightness M represents the brightness at which the pixel value is lower than 20% of the maximum value P for the first time from the brightness X to brightness 245, and the brightness N represents the brightness at which the pixel value is lower than 20% of the maximum value P for the first time from the brightness X to brightness 10.
Citation Information
Patent Citations
Toner
JP2014130243A
Toner
CN103562799A
Toner
CN104345589A